Consumer Behavior toward E-Commerce among Youth of Kathmandu - Khadka, Nil Bahadur; Adhikari, Subash; Lama, Padam Bahadur (International Journal of Atharva, 2025)
The purpose of this study was to find the online shopping experience and factors driving the young consumers towards online shopping in Kathmandu, Nepal, through which, exclusive scenario of the online shopping status among the young consumer was derived, which helped the existing online companies to know their strengths and weaknesses. The empirical part of the study was conducted via quantitative research method i.e. online survey. The data collection was implemented via survey questionnaires. Web-site of free online survey was used to collect the data and the obtained data was derived in Microsoft Excel format for the easy interpretation of the data. The research revealed that the existing online shoppers in Kathmandu are price sensitive. Customers are expecting the product to be precisely as descripted in the website along with smooth customer and after sale service. Opinions from friends and families and the company’s rating directly influence their buying behavior. Flexible payment systems are also highly expected by the customers.